Optimal commodity taxation and redistribution within households - Olivier Bargain; Olivier Donni (Institute for the Study of Labor (IZA), 2011)
Using a collective model of consumption, we characterize optimal commodity taxes aimed at targeting specific individuals within the household. The main message is that distortionary indirect taxation can circumvent the agency problem of the household. Essentially, taxation should discourage less the consumption of a certain group of goods: those for which the slope of the Engel curves is larger for the targeted person.
urn:nbn:de:101:1-201104134471
Keywords: D13; D31; D63; H21; H31; 330; optimal commodity taxation; targeting; intrahousehold distribution; Verbrauchsteuer; Optimale Besteuerung; Privater Haushalt; Familie; Verteilungswirkung; Konsumentenverhalten; Mikroökonomische Konsumfunktion; Theorie